The business of education - Abd Razak, Dzulkifli (2010)
THERE is a slogan adopted by many winning sports teams the world over which reads: "Be the best by recruiting only the best!" It simply means that success is ensured if you take on as many of the "best" people that you need to do a job, give them a target to meet (such as scoring goals) and then reward them well. If they the fail to deliver, then fire them and hire others.